Evaluation preparation technology of Xiaochaihu granules using fingerprint-peak pattern matching - Yu-Qiong Wu; Yu-Qiang Gou; Jing Han; Ying-Yan Bi; Shi-Lan Feng; Fang-Di Hu; Chun-Ming Wang (Elsevier, 2011)
An approach was proposed to evaluate preparation technology by means of fingerprint-peak matching technology of high Performance liquid chromatography with diode array detector (HPLC-DAD). Similarity and hierarchical clustering analysis (HCA) were applied to identify the 15 batches of Xiaochaihu granules from different manufacturers and our laboratory, and peak pattern matching between the composite formulae and Radix Bupleuri Chinensis, which was one of the main ingredients of Xiaochaihu granules, was utilized to evaluate the preparation technology of Xiaochaihu granules via the indexes of the relative deviation of retention time (RT) and UV spectrum feature similarity of their corresponding peaks. Eleven matching peaks were found between Xiaochaihu granules and Radix Bupleuri Chinensis. However, the saikosaponin A and saikosaponin D, which are the important active components in Radix Bupleuri Chinensis, were not found in Xiaochaihu granules from any manufacturers. The peak areas of 11 characteristic peaks of Xiaochaihu granules samples formed a matrix of 11 × 15. The result of HCA showed that Xiaochaihu granules samples were divided into four kinds of category. Xiaochaihu granules samples from the same manufacturer were basically clustered of the same category. The results suggested that the saikosaponin A and saikosaponin D are prone to structural transformation under the condition of decoction and in the presence of the organic acidic components. These active components, existing in raw herb, might transform to a series of non-active secondary saikosaponin due to unfavourable preparation technology. So the conventional decoction-based preparation technology of Xiaochaihu granules might greatly affect its quality and therapeutic effectiveness. This study demonstrates that fingerprint-peak matching technology can not only be used for quality control of this composite formulae, but also provide some guidance for preparation technology of Xiaochaihu granules. Keywords: Xiaochaihu granules, Radix Bupleuri Chinensis, fingerprint-peak matching, hierarchical clustering analysis